Shoe signature monitoring for advanced running technique - Young, C.; Fleming, P. R.; Dixon, S.; Carre, M. J. (The Engineering of sport 7, Volume 2, 2008)
An athlete and support team will utilise whatever tools are at their disposal to help 'measure' the athletic ability and develop it further. However, assessment of the athletic motion technique and propulsion mechanics is usually limited to a combination of indirect techniques (visual, high-speed video etc.) and may include some direct measurement of foot-surface contact forces or pressures in a controlled laboratory environment. The next logical Step in research and development is to provide high quality information of the foot-surface interaction during the athlete's motion in training by the development of advanced instrumentation attached in some way. This information could provide enormous benefits to individuals to both enhance their performance and also provide unique feedback on their (more controlled) rehabilitation from injury. This paper describes findings to date from a current EPSRC/UK Sport funded study to evaluate, in the first instance, what and how appropriate feedback could be given to elite athletes and their coaches of their running characteristics. The research undertaken thus far has elicited the detailed user requirements from a series of Interviews and workshops with elite coaches and athletes and sets out a framework for delivering appropriate technology directly tailored to both measure and enhance performance. The qualitative data is presented as a hierarchical graphical plot showing the six general dimensions (technique, footwear and surface, environment, performance, injury and cardiovascular). These are discussed in detail in turn, with regard to the instrumentation technology required for delivery, and with an emphasis on ideal processed data visualisation techniques required for relatively simple absorption and actions by the athlete and coaching team.